Repeatability of left ventricular dyssynchrony and function parameters in serial gated myocardial perfusion SPECT studies - Lin, Xianhe (2010)
BACKGROUND: The purpose of this study was to establish the repeatability of left-ventricular (LV) dyssynchrony and function parameters measured from serial gated myocardial perfusion SPECT (GMPS) studies. METHODS: Thirty patients, who met standard criteria for cardiac resynchronization therapy (CRT), were prospectively enrolled. One hour after resting injection, a standard GMPS was performed, and repeated 30 minutes later after repositioning the patient. The two serial studies were processed blinded from each other by an experienced operator, and processed side-by-side by another experienced operator using iterative reconstruction, Butterworth filtering, and the Emory Cardiac Toolbox with phase analysis. Phase standard deviation, phase histogram bandwidth, LV ejection fraction, end-systolic volume, and end-diastolic volume were calculated and compared. RESULTS: All measured parameters were highly correlated (r > .90) between the serial studies without significant difference by paired t test. The variations of the parameters measured by side-by-side processing were significantly smaller than those measured by blinded processing. CONCLUSION: These results indicated high repeatability of LV dyssynchrony and function parameters when measured serially by GMPS, especially when the serial studies were processed side-by-side. The measured variations of these parameters can be used to evaluate changes in LV dyssynchrony and function measured by GMPS before and after CRT.